Anatomical characterization of Semi-arid Bignoniaceae using light and scanning electron microscopy - Romisha Sonia; Shabnum Shaheen; Muhammad Waheed; Sana Imran; Shiekh Marifatul Haq; Murad Muhammad; Abeer Hashem; Samiha Al Shehri; Elsayed Fathi Abd-Allah (BMC Plant Biology)
Abstract Background The present research work was done to evaluate the anatomical differences among selected species of the family Bignoniaceae, as limited anatomical data is available for this family in Pakistan. Bignoniaceae is a remarkable family for its various medicinal properties and anatomical characterization is an important feature for the identification and classification of plants. Methodology : In this study, several anatomical structures were examined, including stomata type and shape, leaf epidermis shape, epidermal cell size, and the presence or absence of trichomes and crystals (e.g., prisms, raphides, and druses). Three statistical tools—heat map analysis, correlation analysis, and principal component analysis (PCA)—were used to highlight distinctions and similarities among the species. Results On both the upper and lower leaf surfaces, polygonal, irregular, and hexagonal epidermal cells with thick cell walls were observed. Three patterns of anticlinal cell walls were detected: curved, straight, and sinuous. Distinct stomatal types were also identified across the different species. For instance, sunken stomata were observed in Kigelia africana and Jacaranda mimosaefolia, while anomocytic stomata were found in Oroxylum indicum, Pyrostegia venusta, Tecoma stans, Tecomella undulata, Mansoa alliacea, Heterophragma adenophylla, Handroanthus impetiginosus, Campsis radicans, and Anemopaegma chamberlaynii. Paracytic stomata were examined in B. callistegioides and Dolichandra unguis-cati. Tabebuia aurea was the only species with Tetracytic stomata. A contiguous type of stomata was only observed in Millingtonia hortensis. This family contained three types of trichomes. Glandular peltate trichomes contained a basal epidermal cell, a very small monocellular stalk and a circular or round multicellular head containing 12 cells arranged in a single circle. Non-glandular trichomes had a thin apex without a head and a pointed end. Branched trichomes contained several arms arising from a common base. Conclusion This anatomical examination, using advanced microscopic techniques, is the first to classify several species that are not listed in the e-flora of Pakistan. Leaf anatomical research has proven valuable in resolving challenging taxonomic issues.